Semaphorin-3A Promotes Degradation of Fragile X Mental Retardation Protein in Growth Cones via the Ubiquitin-Proteasome Pathway - Takabatake, Masaru; Goshima, Yoshio; Sasaki, Yukio (Frontiers in Neural Circuits, 2020)
Fragile X mental retardation protein (FMRP) is an RNA binding protein that regulates local translation in dendrites and spines for synaptic plasticity. In axons, FMRP is implicated in axonal extension and axon guidance. We previously demonstrated that FMRP is involved in growth cone collapse translation-dependently in response to Semaphorin-3A (Sema3A), a repulsive axon guidance factor. In the case of attractive axon guidance factors, RNA binding proteins, such as zipcode-binding protein 1 (ZBP1), accumulate towards stimulated side of growth cones for local translation. However, it remains unclear how Sema3A affects FMRP localization in growth cones. Here, we show that level of FMRP in growth cones of hippocampal neurons decreased after Sema3A stimulation. This decrease in FMRP level is suppressed by PYR-41 (ubiquitin-activating enzyme E1 enzyme inhibitor) and MG132 (proteasome inhibitor), suggesting that ubiquitin-proteasome pathway is involved in the Sema3A-induced FMRP degradation in growth cones. These E1 enzyme and proteasome inhibitors suppressed Sema3A-induced increase in microtubule associated protein 1B (MAP1B) in growth cones, suggesting that ubiquitin-proteasome pathway regulates local translation of MAP1B whose translation is mediated by FMRP. These inhibitors also blocked Sema3A-induced growth cone collapse. Our results suggest that Sema3A promotes degradation of FMRP in growth cones via ubiquitin-proteasome pathway, leading to growth cone collapse via local translation of MAP1B. These findings raise the new mechanism to regulate axon guidance by degradation of the translational suppressor FMRP by ubiquitin-proteasome pathway.